INTERNASIONAL JUANDA DALAM MENJEMBATANI KELUHAN KONSUMEN DI MASA PANDEMI COVID-19 - Firdaus Juliansyah; Yulis Nila Sari; Renada Audri Suhariono; M. Syahrul Munir; Carlos Antonio Lopulalan; Dyva Claretta; Dian Hutami Rahmawati (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The Covid-19 pandemic is currently a significant polemic in various countries; one of the areas affected is the aviation sector. Juanda International Airport, which is included in this sector, has not been spared the impact caused by the pandemic. Therefore, people who want to take a flight need to find out the information and requirements before leaving. There are not infrequently consumers who complain about this through social media or call centers. This study aims to determine the response and strategy given by Juanda Airport Public Relations to bridge consumer complaints. The methodology used is descriptive qualitative with taking informants using the purposive sampling method. As a reference in the research theory, the Organization-Public Relationship (OPR) consists of four dimensions: control mutuality, trust, satisfaction with a relationship, and commitment to a relationship. This study was conducted to determine Juanda Airport's attitude or public relations strategy in bridging consumer complaints during the Covid-19 pandemic. Based on the results of the study, it was found that the implementation of the activities carried out by public relations at Juanda Airport was following the OPR theory, and in responding to consumer complaints on social media, public relations always prioritized a humanist and persuasive approach, to create relationships and responses between humans, not results from robots